Biometric Banking: Evaluating the Effectiveness of Arduino-Integrated Fingerprint Systems for Locker Security - Navneet Kaur; Nidhi Ahirwar; Mohini Prasad; Ankit Sharma; Chetan Bhaisare (International Journal of Electrical Power and Machine Systems, 2024)
The aim of this research paper is to implement a fingerprint-based bank locker system using Arduino that provides enhanced security features for users. The proposed system eliminates the need for traditional keys and instead utilizes biometric identification to grant access to the locker. The inexpensive and user-friendly Arduino microcontroller platform is used to design the system. The proposed system is implemented using various sensors, including fingerprint sensors, keypad, and LCD display. The system also includes a GSM module, which sends alerts to the user's mobile phone in case of any unauthorized access attempt. To overcome these issues, the proposed system utilizes biometric identification to grant access to the locker. The system also includes features such as remote monitoring and alerting, making it a highly secure friendly solution. This system is more secure than any other since it makes use of identity, security question approach, RFID technology, and GSM technology.
Keywords: Arduino; GSM (Global System for Mobile Communication); LCD (Liquid Crystal Display); RFID (Radio Frequency Identification); SMS (Short Message service)